Water Availability and Row Spacing Effects on Nitrogen Use Efficiency in No-Till Maize - Barbieri, Pablo; Echeverria, Hernan Eduardo; Sainz Rozas, Hernan Rene (Scholars Direct, 2023)
Reduced row spacing has shown to increase nitrogen use efficiency (NUE) in no-till irrigated maize; however available information in rainfed conditions is scarce. The objective was to analyze row spacing effects on NUE under different water and nitrogen (N) regimes. Maize crops were grown at Balcarce, Argentina, during two seasons. Treatments included two water regimes (rainfed and irrigated), two rows spacing (35 and 70 cm) and two N rates (0 and 180 kg N ha-1). Nitrogen rate and narrow rows increased total dry matter (DM), grain yield, and DM and grain N accumulation in both water regimes. In both years and water regimes, narrow rows increased NUE. Physiological efficiency decreased with N rate and was not affected by row spacing. Recovery efficiency (RE) decreased with N rate, and wide rows spacing. Narrow rows effects on RE decreased as N availability increased. Narrow rows increased NUE largely as a result of increased RE. Greater RE for narrow rows treatments was evident since early growth stages (V6). Average two growing seasons, grain yield and NUE response to narrow rows was higher for rainfed condition and/or N deficient crops than maize with high N rate and irrigation. Results shown that narrow rows increased NUE in no-till maize under rainfed conditions.